1990
DOI: 10.1093/ije/19.3.559
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Infarction is Inversely Associated with Plasma 25-Hydroxyvitamin D3 Levels: A Community-Based Study

Abstract: The relation between the plasma level of 25-hydroxyvitamin D3, the main metabolite of sun-induced vitamin D, and myocardial infarction (MI) was investigated in a community-based case-control study. Some 179 MI patients presenting to hospital within 12 hours of the onset of symptoms were individually matched with controls by age, sex and date of blood collection. MI patients had significantly lower mean 25-hydroxyvitamin D3 levels than controls (32.0 versus 35.5 nmol/L; p = 0.017), with the case-control differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
194
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 356 publications
(212 citation statements)
references
References 0 publications
12
194
1
5
Order By: Relevance
“…Additionally, studies have suggested that low concentrations of vitamin D are related to cardiovascular disease, myocardial infarction, stroke, and congestive heart failure [38,39,40]. It is known that vitamin D plays an important role in the regulation of cholesterol biosynthesis.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Additionally, studies have suggested that low concentrations of vitamin D are related to cardiovascular disease, myocardial infarction, stroke, and congestive heart failure [38,39,40]. It is known that vitamin D plays an important role in the regulation of cholesterol biosynthesis.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The first case-control studies to use the newly developed assay for 25(OH)D found, unexpectedly at the time, that myocardial infarction cases had similar or lower 25(OH)D levels than controls (90)(91)(92) . The initial test of the hypothesis Vitamin D and public health that vitamin D may protect against CVD was a populationbased case-control study from New Zealand, published in 1990, which found a significant inverse association between 25(OH)D levels and risk of myocardial infarction (93) . However, because of the case-control design with collection of blood samples after the onset of disease, uncertainty remained as to whether or not 25(OH)D levels in cases had been affected by the disease process.…”
Section: Cvdmentioning
confidence: 99%
“…In New Zealand, reported sunlight exposure has been shown to correlate with serum 25(OH)D concentrations (25) .…”
Section: Statistical Analysesmentioning
confidence: 99%